2010
DOI: 10.1007/s00134-010-2012-4
|View full text |Cite
|
Sign up to set email alerts
|

Secondary adrenal insufficiency in the acute phase of pediatric traumatic brain injury

Abstract: Secondary AI is frequent during the acute phase of pediatric TBI, particularly when intracranial hypertension is present. Systematic assessment of pituitary function after TBI appears to be essential. A randomized clinical trial is warranted to evaluate the benefits of hormonal replacement therapy in TBI patients with AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In children, most cases appear to be diagnosed by 6 months after injury, with the majority of cases resolving within 1 year. [59][60][61][62][63][64][65][66] In the current experiments, significant decreases in either GH or IGF-1 were not present in single injury animals. In the RTBI group, IGF-1 was significantly reduced at 1 week, and continued to be low at 1 month, whereas GH was only significantly decreased at 1 month after injury.…”
Section: Incidence and Time Course Of Hormonal Changesmentioning
confidence: 91%
“…In children, most cases appear to be diagnosed by 6 months after injury, with the majority of cases resolving within 1 year. [59][60][61][62][63][64][65][66] In the current experiments, significant decreases in either GH or IGF-1 were not present in single injury animals. In the RTBI group, IGF-1 was significantly reduced at 1 week, and continued to be low at 1 month, whereas GH was only significantly decreased at 1 month after injury.…”
Section: Incidence and Time Course Of Hormonal Changesmentioning
confidence: 91%
“…Although HPA axis alterations have been described in children suffering from meningococcal sepsis [10][11][12], the dynamics, drivers and prognostic value of systemic cortisol availability in the broader population of critically ill children have only scarcely been investigated [13,14]. Nevertheless, studies have suggested that a substantial proportion of critically ill children may not be able to increase systemic cortisol availability enough to face the stress of the critical illness, which could cause hemodynamic instability and systemic hyperinflammation with need for vasopressor support [15,16]. As a consequence, pediatric intensivists often prescribe systemic corticosteroids, often in quite high doses, although adequately powered RCTs investigating its clinical efficacy and safety in children are lacking [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dupuis et al 5 reported that 36% of pediatric patients with TBI have secondary AI. Since it can be life-threatening, AI in the acute phase of TBI has received special attention 6 7.…”
Section: Introductionmentioning
confidence: 92%